Deploying the Line to Study Young Adults' Material-Discursive Identity Work and Its Slippery-Sticky Attachments to Developmentalism: A Diffractive Analysis. (March 2023) - Clark/Keefe, Kelly; Becker, Kelly Mancini; White, Erika R.
This article shares what surfaced during diffractive analysis of data from a participatory arts-engaged research project called Life Lines. Drawing on material feminism, studio-inquiry practices were designed to assist young adults in creatively speculating alongside researchers over varied conceptualizations of identity, including dominant explanations centering on cognitive development and alternative framings emphasizing materiality's role in subjective formation. Lines as both culturally inscriptive "engines of theory" and as materially sensitive artistic inquiry practices were enlisted to open new insights about how it is for young adult bodies to sustain developmentalism's "cruel optimism" about coherence, stability, and progression.